Water quality modelling and artificial neural network - Jami, Mohammed Saedi; Zainudin, Zaki (International Water Association (IWA), 2012)
Water quality modelling and artificial neural network, IWA Specialist Group Directory, Global Trends & Challenges in Water Science, Research and Management, A compendium of hot topics and features from, IWA Specialist Groups,